Estrategias de afrontamiento y Autoestima en Estudiantes de nivelación. Universidad Nacional de Chimborazo. Riobamba, 2018 - Castro Chicaiza, Johana Estefanía (2019)
The present research project was carried out in the "National University of Chimborazo," the objective of the study was to analyze the coping strategies and the self-esteem in the leveling students of the Faculty of Health Sciences, sample formed by 240 students in ages between 18 and 23 years of age. The type of research was cross-sectional, using the Lazarus Coping Scale to measure coping strategies and Stanley Coopersmith's Self-Esteem Inventory to assess self-esteem levels. Among the most relevant results of the statistical analysis, it determined that 27.5% of the students use the Acceptance of Responsibility and 22.5% the Positive Reevaluation, being these the coping strategies mostly used by the students, contrary to the eight plans the least used is Confrontation with 0.42%. Within the inventory applied to assess self- esteem levels, it can seen that 25.42% of students retain high self-esteem, 38.33% average self-esteem, and with low self-esteem 36.25%. According to the results obtained, a psych educational intervention guide was designed to improve self-esteem and strengthen the coping strategies of the leveling students of the Faculty of Health Sciences of the National University of Chimborazo.